Developmental and Functional Control of Natural Killer Cells by Cytokines - Wu, Yang; Tian, Zhigang; Wei, Haiming (Frontiers in Immunology, 2017)
Natural killer (NK) cells are effective in combating infections and tumors and as such are tempting for adoptive transfer therapy. However, they are not homogeneous but can be divided into three main subsets, including cytotoxic, tolerant, and regulatory NK cells, with disparate phenotypes and functions in diverse tissues. The development and functions of such NK cells are controlled by various cytokines, such as fms-like tyrosine kinase 3 ligand (FL), kit ligand (KL), interleukin (IL)-3, IL-10, IL-12, IL-18, transforming growth factor-β, and common-γ chain family cytokines, which operate at different stages by regulating distinct signaling pathways. Nevertheless, the specific roles of each cytokine that regulates NK cell development or that shapes different NK cell functions remain unclear. In this review, we attempt to describe the characteristics of each cytokine and the existing protocols to expand NK cells using different combinations of cytokines and feeder cells. A comprehensive understanding of the role of cytokines in NK cell development and function will aid the generation of better efficacy for adoptive NK cell treatment.